912 Cleaning and disinfection in home healthcare: integrating qualitative and quantitative methods to assess caregivers' exposure to cleaning and disinfection products. (24th April 2018) - Markkanen, Pia; Quinn, Margaret; Goodyear, Nancy; Galligan, Catherine; Kriebel, David; Sama, Susan; Gore, Rebecca; Lindberg, John; Beato-Melendez, Christian; Karlsson, Nicole; Mohamed, Hagir; Sheikh, Noor; et al.
Abstract : Introduction: In the United States, home care (HC) aide is one of the fastest growing jobs. Aides perform both personal care and cleaning and disinfection (C and D) tasks in the clients' homes. There is clear scientific evidence of asthma and other respiratory effects with C and D work. This presentation demonstrates how mixed research methods assessed the nature of C and D work and health-related exposures in HC. Methods: The Safe Home Care Project conducted 9 focus groups comprising 80 HC aides and 5 in-depth interviews with HC employers' and workers' representatives. All focus groups and interviews were audio-recorded and transcribed verbatim. Computer-assisted thematic analysis of all transcripts was conducted. The results informed the development of (i) the microbiology field study in 46 seniors' homes to measure micro-organisms and soil on common household surfaces and how effectively 'green' and bleach-containing products cleaned these surfaces, and (ii) the laboratory study to measure airborne C and D product exposures among HC aides (n=20) who performed C and D tasks in a simulated bathroom with 4 different products. Result: HC aides sanitise bathrooms and kitchens frequently. Bleach-containing products are commonly applied and HC clients mostly decide which C and D products are used. The microbiology study showed that both 'green' and bleach-containing products removed micro-organisms on tested surfaces. The laboratory study showed that the bleach-containing cleaning product generated high airborne chlorine exposures: over 60% of the aides exceeded 1 ppm for chlorine – a permissible exposure limit of the US Occupational Safety and Health Administration. Discussion: Mixed methods research techniques provide complementary data for assessing and characterising C and D exposures in HC. Use of bleach-containing products can generate high airborne chlorine exposures. Chlorine is a respiratory irritant. It seems prudent to limit the unnecessary use of bleach in HC and carefully discern – on a client-by-client basis – whether bleach is needed for infection prevention.